KOLABORASI DALAM PENGELOLAAN PERKEBUNAN KELAPA SAWIT RAKYAT (STUDI KASUS: KUD LUBUK KARYA DAN KUD KAMPUNG SURAU KAB. DHARMASRAYA - Yulistriani (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
Palm oil is an export commodity that has an important role in the people's economy. Plasma patterns often experience problems after being released from large plantations. Cooperation between oil palm business actors influences the development of the people's oil palm business, especially in Dharmasraya Regency. This study aims to look at the impact of the development of smallholder oil palm plantations on the economic development of rural communities (case study: KUD Lubuk Karya and KUD Kampung Surau).The method used in this research is descriptive qualitative method. Data obtained through in-depth interviews with key informants. The results showed that the KUD Lubuk Karya had a greater influence on the economy of the village community. Collaboration with the principle of justice, a common understanding of the responsibilities of each party strengthens the existence of the KUD in accelerating village development. It is necessary to evaluate, innovate and provide optimal assistance for the sustainable development of smallholder palm oil plantations